Mediating Economic Growth toward Inclusive Development: State Institutional Capacity and the Developmental Role of BPJS Ketenagakerjaan in Indonesia - Julizar Idris; Abdul Gaffar Karim; Abdul Wahab Samad; Arif Nugroho (Jurnal Multidisiplin Sahombu, 2025)
This article examines BPJS Ketenagakerjaan as a manifestation of state institutional capacity in mediating the transformation of economic growth into inclusive development in Indonesia. Challenging growth centred development assumptions, the study argues that labour welfare outcomes depend on institutional mediation rather than macroeconomic expansion alone. Using a qualitative institutional and public policy analysis based on statutory documents, official reports, labour market data, and peer reviewed literature, the study identifies three key mechanisms. First, BPJS Ketenagakerjaan strengthens social fiscal and administrative capacity through expanding coverage and long term fund accumulation. Second, it institutionalises collective risk pooling that stabilises labour incomes amid market volatility. Third, its long horizon funds exhibit potential to function as public patient capital for development financing, conditional on governance quality. The findings reposition employment based social security as an active developmental institution rather than a residual welfare instrument. The study contributes to development economics and public administration by extending social investment and state capacity debates to developing economies with high labour informality.